Climate warming and heat waves affect reproductive strategies and interactions between submerged macrophytes. (19th July 2016) - Li, Zhongqiang; He, Liang; Zhang, Huan; Urrutia‐Cordero, Pablo; Ekvall, Mattias K.; Hollander, Johan; Hansson, Lars‐Anders
Abstract: Extreme climatic events, such as heat waves, are predicted to increase in frequency and intensity during the next hundred years, which may accelerate shifts in hydrological regimes and submerged macrophyte composition in freshwater ecosystems. Since macrophytes are profound components of aquatic systems, predicting their response to extreme climatic events is crucial for implementation of climate change adaptation strategies. We therefore performed an experiment in 24 outdoor enclosures (400 L) separating the impact of a 4 °C increase in mean temperature with the same increase, that is the same total amount of energy input, but resembling a climate scenario with extreme variability, oscillating between 0 °C and 8 °C above present conditions. We show that at the moderate nutrient conditions provided in our study, neither an increase in mean temperature nor heat waves lead to a shift from a plant‐dominated to an algal‐dominated system. Instead, we show that species‐specific responses to climate change among submerged macrophytes may critically influence species composition and thereby ecosystem functioning. Our results also imply that more fluctuating temperatures affect the number of flowers produced per plant leading to less sexual reproduction. Our findings therefore suggest that predicted alterations in climate regimes may influence both plant interactions and reproductive strategies, which have the potential to inflict changes in biodiversity, community structure and ecosystem functioning.